Inositol polyphosphate multikinase regulates Th1 and Th17 cell differentiation by controlling Akt-mTOR signaling - Chae Min Yuk; Sehoon Hong; Dongeon Kim; Mingyo Kim; Hyun-Woo Jeong; Seung Ju Park; Hyungyu Min; Wooseob Kim; Jongbu Lim; Hyo Dam Kim; Sang-Gyu Kim; Rho Hyun Seong; et al. (Cell Reports)
Summary: Activated proinflammatory T helper (Th) cells, including Th1 and Th17 cells, drive immune responses against pathogens and contribute to autoimmune diseases. We show that the expression of inositol polyphosphate multikinase (IPMK), an enzyme essential for inositol phosphate metabolism, is highly induced in Th1 and Th17 subsets. Deletion of IPMK in CD4+ T cells leads to diminished Th1- and Th17-mediated responses, reducing resistance to Leishmania major and attenuating experimental autoimmune encephalomyelitis. IPMK-deficient CD4+ T cells show impaired activation and Th17 differentiation, linked to the decreased activation of Akt, mTOR, and STAT3. Mechanistically, IPMK functions as a phosphatidylinositol 3-kinase to regulate phosphatidylinositol (3,4,5)-trisphosphate (PtdIns(3,4,5)P3) production, promoting T cell activation and effector functions. In IPMK-deficient CD4+ T cells, T cell receptor-stimulated PtdIns(3,4,5)P3 generation is abolished by wortmannin, suggesting IPMK acts in a wortmannin-sensitive manner. These findings establish IPMK as a critical regulator of Th1 and Th17 differentiation, underscoring its role in maintaining immune homeostasis.